What Drives Target2 Balances? Evidence From a Panel Analysis - Raphael A. Auer (Swiss National Bank, Study Center Gerzensee, 2013)
What are the drivers of the large Target2 (T2) balances that have emerged in the European Monetary Union since the start of the financial crisis in 2007? This paper examines the extent to which the evolution of national T2 balances can be statistically associated with cross-border private capital flows and current account (CA) balances. In a quarterly panel spanning the years 1999 to 2012 and twelve countries, it is shown that while the CA and the evolution of T2 balances were unrelated until the start of the 2007 financial crisis, since then, the relation between these two variables has become statistically significant and economically sizeable. This reflects the "sudden stop" to private sector capital that funded CA imbalances beforehand. I next examine how different types of private capital flows have evolved over the last years and how this can be related to the evolution of T2 balances, finding some deposit flight by private customers, a substantial retrenchment of cross-border interbank lending, and also an increase of bank's holdings of high-quality sovereign debt. My first conclusion from this analysis is that since T2 imbalances were caused by a sudden stop and are unlikely to grow without bounds since Euro area CA imbalances are currently diminishing at a rapid pace, there is no evidence that the institutional setup of the European Monetary Union needs to be reformed fundamentally. My second conclusion relates to how the current system transfers risks across the currency union, both in terms of risk transfer from T2 debtor to T2 creditor nations and in terms of risk transfer from the private sector to the public sector within T2 creditor nations. I evaluate existing reform proposals in the light of these risk transfers.
Keywords: 330; Clearing; Finanzkrise; Leistungsbilanz; Außenwirtschaftliches Gleichgewicht; EU-Staaten